Application of biofungicides Bisolbifit and Bisolbisan for protection of cabbage from diseases - Vitaliy N. Gubkin; Lyudmila L. Bondareva (Овощи России)
Relevance The main diseases that affect cabbage crops during the growing season are bacterioses, alternariosis, fusarium and others. Despite the success of breeding to create resistant varieties and hybrids in some years, there is a massive disease defeat of cabbage. Therefore, preventive measures aimed at reducing the level of cabbage diseases are of paramount importance. In recent years, in connection with the development of agricultural biotechnology for the prevention of cabbage diseases, biologics have been proposed based on the products of bacterial metabolism: antibiotics, enzymes, phytohormones, vitamins, etc. Methods In the Laboratory of Cole Crop Breeding and Seed Production of the Federal Scientific Vegetable Center in 2017-2018 conducted tests of biofungicides. The article presents the results of tests of biofungicides BisolbiSana and BisolbiFita to protect cabbage from diseases. Results The biological effectiveness of pre-sowing treatment of seeds and vegetative plants with biofungicides against cabbage altenariosis was 53.3-57.1%, against bacterial mucosa 40.2-47.8% depending on the variety (hybrid). Plant yield increased by 7-8.5%.